Sciences with the Science - Jacques Commaille (Alliance Athena, 2015)
In the current European environment where the main orientations of research are being redefined, it is fit to reconsider the general principles underlying the Social Sciences & Humanities and their place in Science and Society. The need for a fruitful dialogue between sciences in order to cope with the major challenges of today's world invites us to bring again to the fore the figure of 'the engineer' as largely open to humanities. Beyond any specifically scientific consideration, the SSH are addressing anew the question of the purpose of our societies and of the way they will evolve. This study is the result of an exceptional gathering of searchers and scholars. It aims at restoring the SSH back into their deserved position and at promoting male and female scientists dedicated to avoiding the frauds of technicism, dogmatism and scienticism.